Proximate, Fatty Acids, Cholesterol and Alpha-Tocopherol Contents in Selected Marine Fish and Shellfish From West Coast of Peninsular Malaysia - Abd Aziz @ Mughni, Nurnadia (2011)
Fish and shellfish are widely known as highly nutritious food. However, generally people always consider fish from different types are all of the same nutritional value and select fish only based on availability, freshness, flavour and other physical factors. Thus, to increase awareness on nutrient composition of local fish and shellfish among consumers, information on complete nutritional values must be made available. The main objective of the study was to determine and validate the proximate, fatty acids, cholesterol and alpha-tocopherol contents in selected marine fish and shellfish from West Coast of Peninsular Malaysia (WCPM). Stratified random sampling procedurewas used and samples were collected from 10 fish landing areas located along WCPM. Nutritional data were derived from mean of values of the composite samples. Generally, the proximate analysis showed that most samples contained moisture values (70-90%), ash content (1-2%); protein content for fish (18-20%) and for shellfish (13- 16%) samples. Based on the fat contents, nine species of fish samples can be categorized as lean fish (<2% fat); hardtail scad (Megalapsis cordyla), golden snapper (Lutjanus johnii), indian mackerel (Rastrelliger kanagurta), indian threadfin (Polynemus indicus),malabar red snapper (Lutjanus argentimeculatus), dorab wolfherring (Chirocentrus dorab), long-tailed butterfly ray (Gymnura spp.), large-scale tongue sole (Cynoglossus arel), and spanish mackerel (Scromberomorus guttatus). Meanwhile, nine species were categorized as low fat fish (2-4% fat); black pomfret (Parastromateus niger), silver pomfret (Pampus argentus), sixbar grouper (Epinephulus sexfasciatus), japanese threadfin bream (Nemipterus japonicas), yellowstripe scad (Selaroides leptolepis), gray eel-catfish (Plotosus spp.), fourfinger threadfin (Eleutheronema tetradactylum), giant seaperch (Lates calcarifer), and fringescale sardinella (Clupea fimbriata); moonfish (Trachinotus blochii) as medium fat fish (4-8% fat), and longtail shad (Hilsa macrura) as high fat fish (>8% fat). Only four samples contained carbohydrate; fringescale sardinella (Clupea fimbriata), cuttlefish (Sepia officinalis ), cockles (Anadara granosa )and oyster (Ostrea spp.) at 3.07%, 0.87%, 1.51%, and 6.45%, respectively. For micro minerals contents, cockles (Anadara granosa) and oyster (Ostrea spp.)contained significantly higher (p<0.05) levels of cobalt, iron, manganase and zinc compared to other samples. Meanwhile for copper, prawn (Metapenaeus affinis) and oyster (Ostrea spp.) were significantly higher (p<0.05) compared to others. Overall, the contents of micro minerals in all samples were below the permissible limits; except for oyster (Ostrea spp.); with copper slightly higher than the limit set by FAO/WHO (1984),but below the limit set by Malaysian Food Regulation (1985); and zinc content higher than the limit set by Malaysian Food Regulation (1985), but below the limit set by FAO/WHO (1984). Meanwhile for macro minerals, most samples contained comparable sodium contents, significantly lower of potassium contents, higher calcium contents, and extremely higher of magnesium contents compared to the common ranges reported in the literatures. All samples were good sources of other micro and macro minerals and could provide multi-health benefits if consumed in recommended amounts. Quantification of fatty acids in all samples showed that longtail shad (Hilsa macrura),yellowstripe scad (Selaroides leptolepis), and moonfish (Trachinotus blochii) contained significantly higher (p<0.05) amounts of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and alpha-linolenic acid (ALA) contents, respectively. The polyunsaturated /saturated (P/S) ratio for most samples were higher than Menhaden oil(P/S=0.58) (recommended PUFA supplement by Food and Drug Administration), which was beneficial to lower blood pressure. yellowstripe scad (Selaroides leptolepis) (highest DHA, ω-3/ω-6=6.37, P/S=1.71); moonfish (Trachinotus blochii) (highest ALA, ω-3/ω-6=1.88, P/S=0.96); and longtail shad (Hilsa macrura) (highest EPA, ω-3/ω-6=0.76,P/S=0.36) were samples with outstandingly desirable overall composition of fatty acids. Most samples contained low amount of cholesterol, except for sixbar grouper, longtailed butterfly ray, yellowstripe scad (Selaroides leptolepis), cuttlefish (Sepia officinalis), large-scale tongue sole (Cynoglossus arel), and longtail shad (Hilsa macrura) which were fairly high in cholesterol (119.39-353.97 mg/100g wet samples). However, these fish were high in ω-3 fatty acids with desirable ω-3/ω-6 and P/S ratios for lowering blood cholesterol and giving other health benefits. Only a few samples contained alpha-tocopherol, with four of them; indian mackerel (Rastrelliger kanagurta), giant seaperch (Lates calcarifer), prawn (Metapenaeus affinis), and moonfish (Trachinotus blochii) were fairly high of this antioxidant vitamin. Validation procedures proved that methods used for selected nutrients (fatty acids, cholesterol, alpha-tocopherol) analysis were highly accurate and able to produce reliable and precise data.These representative and reliable nutritional data are now available for wide range of local marine fish and shellfish species and would be a very useful reference to people throughout the country.